DNA Damage Response and Repair in Adaptive Immunity - Luo, Sha; Qiao, Ruolin; Zhang, Xuefei (Frontiers in Cell and Developmental Biology, 2022)
The diversification of B cell receptor (BCR), as well as its secreted product, antibody, is a hallmark of adaptive immunity, which has more specific roles in fighting against the pathogens that escape from the innate immunity. The antibody diversification is from recombination activating gene (RAG)-initiated V(D)J recombination, activation-induced cytidine deaminase (AID)-initiated class switch recombination (CSR) and V(D)J exon somatic hypermutation (SHM). Proper repair of the RAG- and AID-initiated DNA lesions and double-strand breaks (DSBs) is required for promoting antibody diversification and suppressing genomic instability and oncogenic translocations. The DNA damage response (DDR) factors and DSB end joining factors are recruited to the RAG- and AID-initiated DNA lesions and DSBs to coordinately resolve them for generating productive recombination products during antibody diversification. Recently, cohesin-mediated loop extrusion has been proposed to be the underlying mechanism of V(D)J recombination and CSR, which plays essential roles in promoting the orientation-biased deletional end joining during V(D)J recombination and CSR. Here, we will discuss the mechanism of DNA damage repair in antibody diversification.